Frequency of curvilinear motion during competitive soccer play - Brice, P.; Smith, N.; Dyson, R. (Journal of Sports Sciences, 2004)
Hauptziel der Studie war die Aufhellung der Päsenz curvilinearer Bewegungen in einem Fußballspiel.